2019
DOI: 10.1053/j.jrn.2019.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Lean Tissue Index and Body Cell Mass Can Be Predictors of Low Free Testosterone Levels in Men on Hemodialysis

Abstract: Objective: Testosterone deficiency is a common disorder among men treated with hemodialysis. The aim of our study was to evaluate the relationship between free testosterone levels and body composition, biochemical markers of nutritional status, and inflammation in men on hemodialysis.Design: Prospective analysis of men treated with hemodialysis for more than 3 months in one hemodialysis center. Subjects: A total of 56 men-41 men undergoing hemodialysis treatment thrice-weekly over a period of at least 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…28 Another study assessing FT levels and LTI in men on hemodialysis also confirms these results in a CKD population. 29 On the other hand, the study by Amiri et al revealed that a hypogonadal state increased the hazard ratio of developing CKD in males by 1.26 in comparison to eugonadal men. 30 Aside from the influence of testosterone levels on muscle mass, this anabolic hormone can also affect fat tissue.…”
Section: Discussionmentioning
confidence: 97%
“…28 Another study assessing FT levels and LTI in men on hemodialysis also confirms these results in a CKD population. 29 On the other hand, the study by Amiri et al revealed that a hypogonadal state increased the hazard ratio of developing CKD in males by 1.26 in comparison to eugonadal men. 30 Aside from the influence of testosterone levels on muscle mass, this anabolic hormone can also affect fat tissue.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, there are several theoretical explanations for sex differences in muscle wasting, including the anabolic effects of testosterone, and the anti-inflammatory effects of estrogen [42,43]. Testosterone deficiency is especially common in male dialysis patients with low muscle mass [44] and this may have contributed to the greater LTM loss over time. Conversely, estrogen may have exerted an anti-inflammatory effect in the premenopausal women included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes of the wasting are an inadequate calorie intake, reinforced by a diminished appetite due to uremia, multiple comorbid hormonal disorders (insulin and insulin IGF-1 resistance, hypogonadism, hyperparathyroidism) and metabolic acidosis, inhibiting protein synthesis. The disturbances are more strongly expressed along with the progression of CKD [10,30,31].…”
Section: Discussionmentioning
confidence: 99%